Antibiotic consumption and healthcare associated infection in a third level Italian hospital. (30th September 2020) - Gori, F; Vonci, N; Tinturini, A; Basagni, C; Messina, G; De Marco, F
Abstract: Background: The extended length of stay (LoS) is one of the main causes of hospital infections (HAI), followed by an increase in antibiotics consumption. The final step is the development of multiresistant microorganisms, with a consequent increase in costs for the national healthcare system. Aim of this study is to evaluate the prevalence of HAI and to analyze ATB consumption in a teaching hospital Methods: Between 17-21 June 2019 the infection control team collected the clinical records of 425 patients to perform a point of prevalence analysis (PPA). Eligible patients were hospitalized in surgical and medical wards of the teaching Hospital (615 beds) in Siena, Italy. For each patients according to guidelines of European Centers for Disease Control and Prevention (ECDC 4.2) we searched for evidence of HAI and for all indication of ATB consumption. Data were processed using Stata12 Results: Overall 425 patients have been analyzed (48.24% female), mean age was 60.88 (SD 26.11) years, mean LoS 8.37 (min 1 max 86) days. Patients were admitted mostly in General Medicine wards (48.94%); 34% underwent surgery. 63.8% of patients had Peripheral Venous Catheter, 20% Central Venous Catheter and 31.06% Urinary Catheter. Twenty-nine HAI were discovered (PPA 6.82%); the higher prevalence (19.23%) was in Intensive Care Unit. LoS (OR:1.07;IC95%1.04-1.1) and devices (OR:2.17;IC95%1.39-3.37) were the two variables that significantly influenced the infection risk. Forty-six percent of all patients received ATB, the most used were third generation Cephalosporines (26, 18%), followed by Penicillines (24, 73%). The main use was to treat community infections (62.12%), followed by medical prophylaxis (30.81%) Conclusions: PPA of HAI was 6.82%, comparable to 2017 national PPA (6.5%); prolonged LoS is probably the main cause of this result. Our analysis showed that ATB consumption was quite high, in agreement with the Italian prevalence (44.9%), but the percentage of medical prophylaxis was still high. Key messages: The way to achieve the health care infection control is still long, the length of the hospitalization could be a field to be improved. High consumption of antibiotics for prophylaxis is still the main point to fight in the battle against the multiresistant microorganisms.